Essential role of membrane vesicles for biological activity of the bacteriocin micrococcin P1. Issue 4 (5th April 2022) - Liu, Yao; Liu, Qian; Zhao, Lu; Dickey, Seth W.; Wang, Hua; Xu, Rui; Chen, Tianchi; Jian, Ying; Wang, Xi; Lv, Huiying; Otto, Michael; Li, Min
Abstract: Bacterial membrane vesicles (MVs) have recently gained much attention and have been shown to carry a wide diversity of secreted bacterial components. However, it is poorly understood whether MV carriage is an indispensable requirement for a cargo's function. Bacteriocins as weapons of bacterial warfare shape the composition of microbial communities. Many bacteriocins have pronounced hydrophobicity that is imposed by their mechanism of action, but how they diffuse through aqueous environments to reach their target competitors is not known. Here we show that antimicrobial competitive activity of an exemplary hydrophobic bacteriocin of the thiopeptide antibiotic family, micrococcin P1 (MP1), is dependent on incorporation into MVs, which were found to carry MP1 at high concentrations. In contrast, MP1 without MV association was poorly active due to low solubility. Furthermore, we provide previously unavailable evidence that MVs fuse with a Gram‐positive bacterium's cytoplasmic membrane, in this case to deliver a bacteriocin to its intracellular target. Our findings demonstrate how bacteria overcome the problem associated with secreting hydrophobic small molecules and delivering them to their target and show that MVs have a key function in bacterial warfare. Furthermore, our study provides hitherto rare evidence that MVs provide an essential rather than merely accessory function in bacterial physiology.